2018
DOI: 10.1093/cdn/nzy071
|View full text |Cite
|
Sign up to set email alerts
|

A Population-Based (Super-Child) Approach for Predicting Vitamin A Total Body Stores and Retinol Kinetics in Children Is Validated by the Application of Model-Based Compartmental Analysis to Theoretical Data

Abstract: BackgroundPublic health nutritionists need accurate and feasible methods to assess vitamin A status and to evaluate efficacy of interventions, especially in children. The application of population-based designs to tracer kinetic data is an effective approach that reduces sample burden for each child.ObjectivesObjectives of the study were to use theoretical data to validate a population-based (super-child) approach for estimating group mean vitamin A total body stores (TBS) and retinol kinetics in children and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 26 publications
1
18
0
Order By: Relevance
“…In retrospect, it seems clear that a less-than-optimal study length led to the unrealistic estimates of DR reported by Cifelli et al (10) for older, well-nourished US and Chinese adults. By including an estimate of vitamin A intake as an additional modeling input in the current analysis, as originally done in our work with López-Teros et al (12) and more recently in a theoretical analysis (26), we obtained revised estimates of vitamin A TBS and DR. Specifically, inclusion of the mean RDA for vitamin A (2.8 µmol/d) as an estimate of intake resulted in predictions (Table 2) of 2.8 µmol/d (US) and 2.9 µmol/d (Chinese) for vitamin A intake, values that are much more realistic given the experimental conditions than the values reported in (10) (15 and 6 µmol/d, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In retrospect, it seems clear that a less-than-optimal study length led to the unrealistic estimates of DR reported by Cifelli et al (10) for older, well-nourished US and Chinese adults. By including an estimate of vitamin A intake as an additional modeling input in the current analysis, as originally done in our work with López-Teros et al (12) and more recently in a theoretical analysis (26), we obtained revised estimates of vitamin A TBS and DR. Specifically, inclusion of the mean RDA for vitamin A (2.8 µmol/d) as an estimate of intake resulted in predictions (Table 2) of 2.8 µmol/d (US) and 2.9 µmol/d (Chinese) for vitamin A intake, values that are much more realistic given the experimental conditions than the values reported in (10) (15 and 6 µmol/d, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, this work describes a promising step forward in compartmental modeling of vitamin A kinetics: specifically, that including reasonable estimates for dietary vitamin A intake as an input during the modeling process leads to realistic predictions of TBS, days of vitamin A stores, and DR from kinetic studies of relatively short duration (10). As a next step, it will be important for investigators to evaluate the accuracy of model predictions when intake data are included by using theoretical data and known values for TBS and kinetic parameters to test the approach, as we have recently done to evaluate other methods (26, 30, 31). It is anticipated that such work will confirm our conclusion that including vitamin A intake data as an additional input when modeling vitamin A kinetics can improve predictions of vitamin A TBS and DR by compensating for less-than-optimal study duration.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, it will be important to re-evaluate the appropriateness of the currently used cutoffs for liver VA concentration for this age group and to establish evidence-based cutoffs for TBS. Furthermore, additional kinetic studies should be performed in children, especially in those with low/deficient VA status; the population-based super-child approach ( 12 , 13 , 75 ) provides a feasible design for obtaining useful information on VA kinetics and VA status. As more information becomes available, the mathematical relationship defined in Equation 1 should provide a valuable tool for future work designed to assess dietary VA recommendations and the efficacy and safety of VA intervention strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Our new method could be included as an enhancement to future population-based (“super-person”) vitamin A kinetic studies, an approach that has been used to study retinol kinetics in children in whom extensive blood sampling is not feasible. In light of population-based studies in children ( 17 , 29–31 ) and nonpopulation-based experiments in adults ( 19 , 25 ), an optimal starting design for a sophisticated super-person study might include 120 subjects, 24 sampling times from 1 h to 42 d, with all subjects sampled at a common time (e.g., 7 d) and each subject sampled at 1 additional time. For samples collected during the first day, plasma would be analyzed for both retinol and REs; retinol only would be measured in later samples.…”
Section: Discussionmentioning
confidence: 99%